Irreversibility and Sensitivity analysis of MHD squeezing various shaped nanofluid flow between parallel permeable disks - Abdul Awal; Md. Sarwar Alam (International Journal of Thermofluids)
The efficiency of the thermodynamic system of a real process strongly depends on the effective controlled of entropy generation rate. The key concern of the present study is to elucidate the entropy generation optimization and sensitivity analysis of the two-dimensional hydromagnetic unsteady squeezing nanofluids flow with different shapes of nanoparticles such as spherical, brick, cylindrical, platelet between two parallel circular disks. The stationary bottom disk is assumed as permeable to generate suction/injunction of the fluid through its porous structure and the top disk squeezes away or towards the bottom disk. Three different nanoparticles such as Co, Ni and Al2O3 with different shapes and water as base fluid has been considered. The system of partial differential equations governing the flow is converted to a coupled of non-dimension ordinary differential equations. Then these non-dimension equations are solved via power series and the solutions are analyzed using Hermite- Padé approximation scheme. The effects of the physical flow parameters on entropy generation rate and Bejan number are inspected graphically. It is detected that entropy generation rate and Bejan profile exhibit the higher value for Co-water nanofluid related to Ni-water and Al2O3-water nanofluids. Regression analysis predicts that the present method is significant. Moreover, sensitivity analysis indicates that the Brinkman number is more influential than the porosity parameter and nanoparticles volume fraction. The optimal solution is also identified based on the highest desirability.